A report on the conservation status of segetal weeds in Tajikistan. (16th September 2014) - Nowak, A; Nowak, S; Nobis, M; Nobis, A; Davis, Adam
Summary Intensification of agriculture has significantly diminished the populations of segetal weeds worldwide in recent decades. Remarkable changes to the entire flora and vegetation of man‐made habitats are being observed in agroecosystems. The present study analyses, for the first time, the threat status of segetal weeds in Tajikistan. A group of 871 weed species were evaluated against IUCN criteria. The assessment of threat status revealed that 214 weed taxa have to be regarded as threatened in Tajikistan, including 18 endemic and four subendemic plants. Five species have been classified as extinct, 27 as critically endangered, 27 as endangered, 39 as vulnerable, 34 as near threatened and 44 as in the 'least concern' category. For 38 species, the threat level was not possible, due to lack of data. The most threatened group of taxa is related to rice paddy fields. Numerous losses and disappearances were also observed in cereal communities. Percentages of threatened species in different chorological groups amounted to 58% in the Irano–Turanian, 17% in the Pluriregional, 11% in the Mediterranean, 9.5% in the Cosmopolitan and 4% in the Euro–Siberian species group. Assessment of the threatened status of the rich segetal flora of Tajikistan affords the opportunity to raise awareness of the value of this group of species in the country and may be useful in the conservation management of arable habitats. The results show that even though agriculture in Tajikistan is still based on traditional management and manual work, weed control causes a serious threat to its segetal flora.